Electrochemical synthesis of cuprous oxide with a cylindrical bipolar reactor - Bisang, Jose Maria (2013)
Background This work analyzes the behaviour of monopolar and bipolar electrochemical reactors with a cylindrical configuration using woven wire meshes as three-dimensional anodes for the production of cuprous oxide. Results Calcium gluconate as an additive diminishes cell voltage because of the depolarization of the hydrogen evolution reaction, and it also avoids the reduction of cuprous oxide to metallic copper. The quality of the powders obtained in a bipolar reactor with three-dimensional anodes is similar to that of a monopolar reactor. Powders containing 97% cuprous oxide were obtained at current densities ranging from 21 to 103 mA cm-2 with current efficiencies near 100%. The bipolar arrangement presents a simpler electrical connection; however, special attention must be paid to some features of construction to minimize the leakage current. Conclusion Cylindrical bipolar electrochemical reactors with three-dimensional anodes show a good performance for the production of cuprous oxide powder